Antidiabetic activity of cobalt–quercetin complex: A new potential candidate for diabetes treatment - Mohamed M. Hassanien, Entsar A. Saad, Kholoud H. Radwan (Journal of Applied Pharmaceutical Science, 2020)
The development of effective, available, safe, and less costly antidiabetic synthetic preparations based on natural products is of quite interest. To our knowledge, the flavonoid-based cobalt–quercetin complex was not tested before for its antidiabetic activities in vivo. Thus, our aim was to investigate the cobalt-quercetin complex’s (CQC) antidiabetic activities compared to the reference drug insulin in diabetic rats. Diabetes was prompted in male rats via one injection of streptozotocin (STZ, 50 mg/kg). Daily, diabetic animals were treated with either a dose of CQC or insulin for 15 days. Water and food intakes, bodyweight changes, total antioxidant capacity (TAC), hemoglobin A1C (HbA1C%), nitric oxide (NO), aspartate aminotransferase (AST) and alanine aminotransferase (ALT), albumin, lipid portrait, malondialdehyde (MDA), fasting blood glucose (FBG), superoxide dismutase (SOD), uric acid, and creatinine levels were assessed. Pancreas and liver tissues were histopathologically examined. STZ-induced insulin-dependent diabetes mellitus (IDDM) developed significant elevations in FBG, HbA1C, AST, ALT, NO, creatinine, urea, uric acid, and MDA levels, along with significant reductions in albumin, TAC, and SOD levels besides marked lipid profile disturbances and tissue histopathological changes. CQC treatment effectively reversed all the studied diabetes-induced changes via its strong antioxidant properties. Antidiabetic effects of CQC and insulin were comparable. Additional validation studies on the considerable CQC antidiabetic effects are needed.
Keywords: Antidiabetic, antioxidant, cobalt–quercetin complex, defensive, hypolipidemic.